Neostigmine® Improves Pancreatic Duct Visualization in Magnetic Resonance Cholangiopancreatography and Could Be a Cheap Alternative for Secretin - Toledo, Paulina F.; Cárdenas, Gonzalo; Berger, Zoltán; Simian, Daniela; Araya, Francisca (Turkish Journal of Gastroenterology, 2022)
Background: To determine the effect of intramuscular administration of Neostigmine® on the visualization of the pancreatic duct on magnetic resonance cholangiopancreatography in patients with recurrent acute pancreatitis or abdominal pain. Methods: We reviewed patients undergoing magnetic resonance cholangiopancreatography followed by a Neostigmine®-enhanced magnetic resonance cholangiopancreatography. Patients with a history of recurrent acute pancreatitis or abdominal pain who had a magnetic resonance cholangiopancreatography where the pancreatic duct was not entirely seen, were selected to undergo a second magnetic resonance cholangiopancreatography 40 minutes after 0.5 mg Neostigmine®. Images were analyzed by 2 radiologists. The diameter of the pancreatic duct was measured in the head, body, and tail of the pancreas on the baseline images and after Neostigmine®. Results: Ten patients were included, with a median age of 33 years (range 15-61). The maximum diameter of the pancreatic duct increased significantly after Neostigmine® administration in all patients, from 1.84 ± 0.98 to 3.41 ± 1.27 mm in the head, 1.34 ± 0.42 mm to 2.5 ± 0.49 mm in the body and 0.72 ± 0.52 mm to 1.78 ± 0.43 mm in the tail (mean ± SD, P < .0001). Neostigmine® helped to provide better detail of the pancreatic duct anatomy in 4 patients. In 2 patients we confirmed pancreas divisum, in another the Santorini duct was not seen on the baseline images but it was clearly visualized after Neostigmine®, and in the fourth patient, Neostigmine® improved visualization of multiple pancreatic duct stenosis. Conclusion: Neostigmine®-magnetic resonance cholangiopancreatography significantly increases the diameter of the pancreatic duct, allowing an accurate morphological evaluation. It could be a cheap alternative to secretin, which is expensive and hardly available. Cite this article as: Toledo PF, Cárdenas G, Berger Z, Simian D, Araya F. Neostigmine® improves pancreatic duct visualization in magnetic resonance cholangiopancreatography and could be a cheap alternative for secretin. Turk J Gastroenterol. 2022;33(8):704-709.